The Relationship between Critical Thinking Skills and Akhlaqul Karimah in Elementary School Students - Subhan, Subhan (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study investigates the relationship between critical thinking skills and the practice of akhlakul karimah (noble character) among fifth-grade elementary students at Madrasah Ibtidaiyah Cokro Aminoto in Ambon, Indonesia. While akhlakul karimah is a core objective of Islamic education, the specific role of critical thinking in its development remains underexplored, particularly within the Indonesian primary education context. Using a quantitative approach, this research employed a psychological scale to measure the critical thinking skills and akhlakul karimah of 61 students. The findings indicate that students' akhlakul karimah is in a